The construction of a national Maori identity by Maori media - Ian Stuart (Asia Pacific Network, 2003)
This article discusses the Maori construction of a national Maori identity by the Maori media, and by Maori radio in particular. It then suggests that this is creating a Maori nation within the state of New Zealand. This is an important development for Maori and for the future of New Zealand society. The article suggests that Maori are creating a fully developed identity as required by the radical democratic theories of Ernesto Laclau and Chantal Mouffe, and, as such, will provide a practical case study of their theories.